Coexistence of sqrt(3)xsqrt(3) and quasi-linear phases of sulfur adsorbed Θ=1/3 on gold (111) substrate - Gómez Carrillo, Sandra Carolina (2011)
We analyze with the aid of density functional theory and molecular dynamics simulations the adsorption of sulfur (S) on a Au(111) surface at different temperatures with a variety of geometries. We have found a new superficial phase in which sulfur atoms form a quasi-linear chain with energies very close to the expected. The results suggest the coexistence of both configurations at T < 300 K. At high temperatures (T > 300 K) it was shown that the sulfur atoms have high mobility which allows their migration among different adsorption sites. At low temperatures, the mobility decreases and a thermal activation barrier of 25-30 meV can be estimated.